Information Technology Challenges: Developments and Potential Impact on Socio Economics in the Next Two Decades - Irman Amri; Ika Safitri Windiarti (Malikussaleh University, Aceh, Indonesia, 2025)
This study aims to analyze the challenges, developments, and potential impacts of information technology (IT) on socio-economic aspects in the next two decades. Using the Systematic Literature Review (SLR) method that follows PRISMA guidelines, this study examines scientific articles from the Scopus database over the past two decades. The results of the study show that technological developments such as artificial intelligence (AI), big data, Internet of Things (IoT), and digitalization have brought significant changes in various sectors, increasing efficiency, productivity, and innovation. Projections for the next two decades indicate that this trend will continue and evolve, with a major impact on the job market, productivity, quality of life, privacy, and social interaction. The study's conclusions emphasize the need to invest in education and skills training to cope with job market changes, as well as the implementation of strict regulations to protect data privacy and security. Research recommendations include increased collaboration between the public and private sectors, equitable development of digital infrastructure, and public education on the healthy use of technology. Thus, this study provides comprehensive insights to optimize the benefits of information technology while anticipating and overcoming its negative impacts.